Correlation between texture, earing behaviour and dissolved carbon and nitrogen. Issue 3 (11th February 2017) - Yan, Y.; Kang, Y.; Mo, Z.; Zheng, X.; Shen, Y.
Abstract : The present study compared the differences of texture and earing behaviour in DR tinplate steel sheets. Dissolved carbon and nitrogen contents were discussed as the principal factor. The 001⟨110⟩ texture component whose earing tendency is higher than that of heterogeneous 111 fibre texture, is harmful for earing property and needed to be reduced to minimum in most cases. The increase of the dissolved carbon and nitrogen contents is responsible for weaker 111 fibre texture and more intense 001⟨110⟩ component. Additionally, a strong 114⟨110⟩ texture component was observed on condition of higher dissolved carbon and nitrogen contents and its formation mechanism was discussed.